INVESTIGATION OF ANGULAR BALL BEARING WEAR - A. L. Savchenko; N. T. Minchenya (Наука и техника)
Wearing process of balls in an angular ball bearing has been investigated in the paper. Force affecting a separator from the side of balls is determined theoretically. Wear rate may be calculated with a formula for abrasive wear while substituting numerical parameter values of the investigated ball bearing for formula symbols.